Investigating staff views on plagiarism in transnational higher education (Journal of Applied Learning and Teaching, 2021)
The views on plagiarism of teaching staff working at four Australian universities operating in Singapore were investigated through a survey and interviews. This was carried out through analysis of their responses to six different plagiarism scenarios, of their replies to open-ended questions and of interview comments. Although staff were found to have a good understanding of the different cases of plagiarism, nearly half of them indicated that they would accept up to 15% of plagiarized material, with 30% of them willing to accept 20% or more. This indicates the need for an improved staff education on plagiarism. Furthermore, the majority of the teaching staff expected their students to plagiarize, implying the need for a more effective teacher - student interaction. A set of interactive measures between faculty, teaching staff and students is recommended to ensure and sustain an environment of academic integrity within the transnational higher education sector.